Development of a secure e-banking scheme using hybrid NTRU-PKI and One-Time-AES password techniques - Osman, Anas Yalman (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
The e-commerce applications are difficult to gain customers online, while it is easy to lose them. The companies are under pressure to provide secure services compared to their online and physical competitors. The main challenges faced while developing e-banking or m-banking systems are: The authentication, non-repudiation, integrity and confidentiality. In addition, the speed of the cryptography algorithm is also an important issue to be discussed in the design and development phase. The main goal of this research is to propose an advanced secure e-banking scheme by using hybrid NTRU-PKI and One-time-AES password techniques. The development of the scheme is presented. It identifies the existing security algorithms that are necessary to develop a strong secure system that is able to prevent attacks and hacking. This thesis proposes a hybrid scheme for improving the security of e-banking transactions. The design and implementation of the hybrid scheme using NTRU and AES technique are highlighted in detail. The steps of the evaluation and the testing of the scheme are presented. This includes the user account creation, activation, and accessing phases. The scheme has proven to be efficient and secure. However its main limitation is the scalability issue, which is out of the scope of this thesis, and can be addressed as a future recommendation.